PIM findings inform the Government of South Africa’s “Operation Vulindlela” - CGIAR Research Program on Policies, Institutions, and Markets (2021)
Operation Vulindlela is a joint initiative of the Presidency and National Treasury of South Africa to accelerate the implementation of structural reforms and support economic recovery.